2020
DOI: 10.1055/a-1069-6760
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic and sonographic findings in a dog with duplex kidney, ureter duplex and ectopic ureterocele

Abstract: A 5-month-old, male French bulldog was presented with a history of urinary incontinence. Abdominal ultrasound showed changes compatible with a ureterocele and a bilobed right kidney. Excretory computed tomographic urography was consistent with right-sided duplex kidney, ureter duplex and ectopic ureterocele. To the authors’ knowledge, this is the first description of a duplex kidney with an ectopic ureterocele diagnosed with ultrasound and contrast enhanced computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Surgical correction is considered the main treatment for ectopic ureter: the choice of surgical technique is based on the characteristics and extent of the alterations, such as the number, morphology and functionality of ectopic ureters, the location and appearance of the ureteral outlet, the functionality of the kidney, and the presence of other concomitant malformations. The neoureterostomy is generally performed in case of intramural ectopic ureter, while the ureteroneocystostomy is the preferred technique in case of extramural ectopic ureter [8,9,[30][31][32]. The indication for the nephroureterectomy is restricted to ectopic ureters with unilateral, nonfunctional, and irreversible alterations of the ipsilateral kidney [1,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical correction is considered the main treatment for ectopic ureter: the choice of surgical technique is based on the characteristics and extent of the alterations, such as the number, morphology and functionality of ectopic ureters, the location and appearance of the ureteral outlet, the functionality of the kidney, and the presence of other concomitant malformations. The neoureterostomy is generally performed in case of intramural ectopic ureter, while the ureteroneocystostomy is the preferred technique in case of extramural ectopic ureter [8,9,[30][31][32]. The indication for the nephroureterectomy is restricted to ectopic ureters with unilateral, nonfunctional, and irreversible alterations of the ipsilateral kidney [1,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Although reports describing urogenital abnormalities are present in literature [3,[8][9][10], the present case is very peculiar as finding an unusual complex of congenital unilateral anomalies found in the urinary tract (ectopic hydroureter, hydronephrosis, and renal dysplasia) and genital system (partial permanence of the Wolffian duct, which evolved into an epididymal-like structure, and testicular agenesis) of an 8year-old, male dog. The congenital anomaly remained asymptomatic up to this age, when an intra-abdominal mass effect caused by the bulky anomalous structures was probably emphasized by acquired prostatic hypertrophy.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Viscera duplications have been widely described in veterinary medicine, affecting primarily the gastrointestinal and urogenital tract. The clinical signs often include abdominal discomfort or urinary incontinence 4,5 …”
Section: Discussionmentioning
confidence: 99%
“…The clinical signs often include abdominal discomfort or urinary incontinence. 4,5 Based on our review of the literature, there are no reported cases of complete splenic duplication in veterinary medicine. Other colleagues described the sonographic assessment of accessory spleens, defined as "splenunculi."…”
Section: Discussionmentioning
confidence: 99%